Revision Rates in Prepectoral Versus Subpectoral Delayed-Immediate Autologous Breast Reconstruction. Issue 3 (May 2021) - Patel, Ashraf A.; Cemaj, Sophie L.; Martin, Shanique A.; Cheesborough, Jennifer E.; Lee, Gordon K.; Nazerali, Rahim S.
Abstract : Introduction: Breast reconstruction in the prepectoral plane has recently fallen into favor. Minimizing the number of revisionary procedures after reconstruction is an important factor in improving patient care, but long-term studies on the effects of prepectoral reconstruction are limited. In this study, we compare the revision rates after delayed-immediate, autologous reconstruction between prepectoral and subpectoral reconstructions. Methods: Postoperative charts for all patients undergoing subpectoral or prepectoral delayed-immediate autologous breast reconstruction were retrospectively reviewed at our single tertiary-care institution between 2009 and 2018. Patient demographics, comorbidities, and oncologic history were recorded. Charts after second stage reconstruction were reviewed for up to eighteen months to determine if revisions were necessary. Data collected included the total number of surgeries performed, the average number of procedures performed during each surgery, and the type of revision that was performed. Statistical tests included the chi squared test, unpaired t-test, and logistic regressions. Results: Data from 89 patients with 125 breast reconstructions were collected. There was a 41.6% of these that were prepectoral reconstructions (P), and 58.4% were subpectoral reconstructions (S). For both groups, nipple sparing, followed by skin sparing mastectomies were most common. Mastectomy rates were not statistically different. Fewer breasts in the prepectoral cohort required any revisions (P, 21.2% vs S, 47.9%; P = 0.002). The subpectoral cohort had higher rates of soft tissue rearrangement (P, 7.7% vs S, 21.9%, P = 0.032), fat grafting (P, 9.6% vs S, 27.4%; P = 0.014), and nipple reconstruction (P: 5.8% vs 20.5%, P = 0.020). Mean follow-up time was not significantly different between patient groups (P, 290.5 days vs S, 375.0 days, P = 0.142). Subpectoral expander placement was found to be the only variable independently predictive of requiring 1 or more revision ( P = 0.034). Conclusions: Breast reconstruction performed in the prepectoral plane is associated with lower overall rates of revisionary surgery. Rates of soft tissue rearrangement, fat grafting, and nipple reconstruction after autologous reconstruction trended higher in subpectoral reconstructions.